Lead detoxification of edible fungi Auricularia auricula and Pleurotus ostreatus: the purification of the chelation substances and their effects on rats - Zhang, Weiwei; Zheng, Xiaojie; Chen, Xiangdong; Jiang, Xuezhen; Wang, Hexiang; Zhang, Guoqing (Frontiers in Nutrition, 2023)
Lead is a global pollutant and raises worldwide concern. Once lead enters the body, it would be distributed all over the body and will accumulate in the brain, bone, and soft tissues such as kidney, liver, and spleen. Chelators used for lead poisoning therapy all have side effects to some extent, and other drawbacks including high cost. Exploration and utilization of natural antidotes become necessary. To date, few substances originating from edible fungi that are capable of adsorbing lead have been reported. In this study, we found two commonly eaten mushrooms Auricularia auricula and Pleurotus ostreatus exhibited lead adsorption capacity. A. auricula active substance (AAAS) and P. ostreatus active substance (POAS) were purified by hot-water extraction, ethanol precipitation from its fruiting bodies followed by ion exchange chromatography, ultrafiltration, and gel filtration chromatography, respectively. AAAS was 3.6 kDa while POAS was 4.9 kDa. They were both constituted of polysaccharide and peptide. The peptide sequences obtained by liquid chromatography combined with tandem mass spectrometry (LC–MS/MS) proved that they were rich of amino acids which side chain contained groups such as hydroxyl, carboxyl, carbonyl, sulfhydryl, and amidogen. Two rat models were established but only a chronic lead-induced poisoning model was employed to determine the detoxification of AAAS/POAS and their fruiting body powder. For rats receiving continuous lead treatment, either AAAS or POAS could reduce the lead levels in blood. They also promoted elimination of the burden of lead in the spleen and kidney. The fruiting bodies were also proved to have lead detoxification effects. Our study is the first time to identify new functions of A. auricula and P. ostreatus to reduce lead toxicity and also provide dietary strategies for the treatment of lead toxicity.